Penggunaan E-Wallet dengan Pendekatan TAM di Jakarta Barat - Hellen Desiyanti; Wulandari Agustiningsih (J-MAS (Jurnal Manajemen dan Sains), 2023)
This study aims to analyze the interest in using E-wallet using the TAM approach in West Jakarta. Technology Acceptance Model (TAM) is a model to test and predict how technology users behave based on perceived usefulness and convenience. This study uses two independent variables, namely perceived usefulness and perceived convenience. The variables of attitude and interest in using technology are also used as mediating variables and dependent variables. The independent variable in this study. Primary data was collected through the distribution of online questionnaires. The researcher used google form to make a questionnaire. The questionnaire uses a Likert scale: a scale of 5 values, namely strongly disagree (STS) with a value of 1, disagree (ST) with a value of 2, Neutral (N) with a value of 3, agree (S) with a value of 4 and Strongly agree (SS) with a value of 5. The sampling technique used the convenience sampling method and processed SPSS. Criteria Samples are taken from consumers who have used e-wallet. The number of samples obtained reached 162 during April-May 2022. The results showed that the perception of usability and perceived convenience influenced the interest of e-wallet users in West Jakarta. In addition, the attitude variable mediates the perception of usefulness and ease of interest in using technology.